Financial markets and the real economy - Cochrane John H (Cheltenham Edward Elgar, 2006)
The author surveys work on the intersection between macroeconomics and finance. The challenge is to find the right measure of ?bad times,? rises in the marginal value of wealth, so that we can understand high average returns or low prices as compensation
Keywords: Finance; Investments; Macroeconomics; Mathematical models